2002
DOI: 10.1016/s0893-133x(02)00296-8
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Responses to Intravenous Infusion of Sodium Lactate in Male and Female Wistar Rats

Abstract: In patients with panic disorder or premenstrual dysphoria, anxiety attacks can be triggered by intravenous administration of sodium lactate. Since respiratory symptoms, such as hyperventilation and shortness of breath, are characteristic features of spontaneous as well as lactate-induced panic, an involvement of central or peripheral chemoreceptors in this reactionIn patients with panic disorder (Liebowitz et al. , 1985Pitts and McClure 1967) or premenstrual dysphoria (Facchinetti et al. 1992;Sandberg et al. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Lactate (1 mol/L, sodium-L-lactate) was infused at a rate of 100 L/min (equivalent to 100 mol/min) for 5 to 33 minutes (n ‫ס‬ 7). Similar protocols have been used in humans as well as in rats (e.g., Peskind et al, 1998;Wikander et al, 1995;Olsson et al, 2002). In the present and the previously published experiments with rats (Wikander et al, 1995;Olsson et al, 2002), the amount of infused Na salt ranges between 0.5 and 3 mmol (or 2 mmol to 12 mmol per kilogram body weight).…”
Section: Animalsmentioning
confidence: 78%
“…Lactate (1 mol/L, sodium-L-lactate) was infused at a rate of 100 L/min (equivalent to 100 mol/min) for 5 to 33 minutes (n ‫ס‬ 7). Similar protocols have been used in humans as well as in rats (e.g., Peskind et al, 1998;Wikander et al, 1995;Olsson et al, 2002). In the present and the previously published experiments with rats (Wikander et al, 1995;Olsson et al, 2002), the amount of infused Na salt ranges between 0.5 and 3 mmol (or 2 mmol to 12 mmol per kilogram body weight).…”
Section: Animalsmentioning
confidence: 78%
“…45 A disturbance of cerebrovascular regulation could contribute to elevated brain lactate responses in PD. 32,33 Lactate is a respiratory stimulant in humans 9 and animals, 26,27 and is a panicogen in PD patients, although the mechanism(s) of these effects are not yet known. Chemosensitive cells in both brainstem and suprapontine regions, including the ventral medulla, locus ceruleus, raphe nuclei, periaqueductal gray, hypothalamus and amygdala, strongly influence the regulation of arousal, as well as respiration and cardiovascular function.…”
Section: Discussionmentioning
confidence: 99%
“…9 The latter reflects lactate's action as a respiratory stimulant. 26,27 Thus, sodium lactate infusion, like hyperventilation, leads to increased production of endogenous lactic acid as a homeostatic response to alkalosis. Of the many published lactate infusion studies, only two examined patient versus control subject comparisons of serum lactate levels matched for total volume of exogenous lactate infused.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Brack et al (52) found that injection of a panicogenic agonist into the PAG of anesthetized rats elicited a hyperpnea, and a hyperpnea is a common feature of a panic attack (12,256,257).…”
Section: Role Of the Pagmentioning
confidence: 99%